2014
DOI: 10.1097/mat.0000000000000097
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Spectral Analysis for Determining Pump Thrombosis in Rotary Blood Pumps

Abstract: Implantation of rotary blood pumps is an established treatment for end-stage heart failure. Anticoagulation is routinely used for reducing pump thrombosis, but this severe complication still occurs in 5-8% of patients. In 105 patients, the sound produced by the left ventricular assist device HeartWare HVAD was prospectively and sequentially recorded. The acoustic spectra calculated by runtime fast Fourier transformation were investigated. Results were compared with respect to patients without thrombotic compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
55
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 15 publications
1
55
0
Order By: Relevance
“…However, the spectra presented in the paper included low‐frequency information. In figures 1 and 3 in the paper of Kaufmann et al , it is observed that the lowest frequency modes are smaller than (about 7 Hz in their figure 1) or equal to (about 10 Hz in their figure 3) the pump rotation frequency. For the pump considered, the authors show that the most indicative condition for pump thrombosis is the existence of a third harmonic of the pump rotation rate, not present in the control group ( P < 0.0001).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, the spectra presented in the paper included low‐frequency information. In figures 1 and 3 in the paper of Kaufmann et al , it is observed that the lowest frequency modes are smaller than (about 7 Hz in their figure 1) or equal to (about 10 Hz in their figure 3) the pump rotation frequency. For the pump considered, the authors show that the most indicative condition for pump thrombosis is the existence of a third harmonic of the pump rotation rate, not present in the control group ( P < 0.0001).…”
Section: Discussionmentioning
confidence: 87%
“…The idea of using acoustic data to aid clinical decision‐making is by no means new. Such means have been proposed for detecting end‐of‐life of LVAD , and detecting thrombosis in implant rotary blood pumps (8,9). Carrying out an in vivo study, Kaufmann et al considered the sound signature of the HeartWare (Framingham, MA, USA) HVAD LVAD System.…”
mentioning
confidence: 99%
“…In 2003, Tanishiro et al 20 showed that arterial sound can be used to detect malrotation in centrifugal LVADs in an in vitro setup, and in 2007, Slaughter et al 21 showed that acoustic changes predicted impending device malfunction in the pulsatile HeartMate XVE. Recently, Hubbert et al 22 showed significant differences in HeartMate II acoustics when inflow and outflow tubing were subject to artificial stenosis and when artificial clots were passed through the pump, and Kaufmann et al 23 showed that thrombus formation in HeartWare ventricular assist device pumps was associated with telltale changes in acoustic spectra. Similar data collection techniques were used in all studies, although particular equipment differed.…”
Section: Discussionmentioning
confidence: 98%
“…Various approaches have been proposed to detect and monitor for thrombus inside blood pumps . Near‐infrared light has traditionally been used as a noninvasive diagnostic tool for clarifying blood components.…”
Section: Discussionmentioning
confidence: 99%
“…Although various approaches have been proposed to detect thrombus inside blood pumps , no established methods currently exist for timely detection of pump thrombus. As thrombus detection may guide clinical management and appropriate ranges of anticoagulation tailored for patients and the various types of MCS devices in use , there is a strong need for tools to detect and monitor pump thrombus in real time.…”
mentioning
confidence: 99%